Triceratops - Nunn, Daniel (Chicago, Ill. : Heinemann Library, 2007)
Discusses the physical and behavioral characteristics of the triceratops, as well as scientific research with triceratops fossils.
Includes index.
03-06.
P-K.
320
Accelerated Reader
Keywords: Triceratops -- Juvenile literature; Dinosaurios -- Literatura juvenil